Microcrystal foaming material and preparation method thereof
By using coal gasified crude slag and filter cake as raw materials, the process steps are simplified and energy consumption is reduced, and the problem of high preparation cost of microcrystalline foaming materials is solved, and a low-cost and green-developed preparation method of microcrystalline foaming materials is realized.
Patent Information
- Application Number
- CN202411745300.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, the preparation cost of microcrystalline foaming materials is too high and the process is complicated, resulting in waste of resources and equipment loss.
The gasified crude slag and filter cake are used as raw materials, and then fired by drying, grinding and mixing with auxiliary materials to prepare microcrystalline foaming materials. This method simplifies process steps and reduces energy consumption and costs.
It realizes the low-cost preparation of microcrystalline foaming materials, reduces resource consumption and equipment losses, is suitable for industrial production, and is in line with the concept of green development.
Smart Images

Figure CN119707298A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of microcrystalline foamed materials, and in particular to a microcrystalline foamed material and a preparation method thereof. Background Art
[0002] Wall heat conduction is a major cause of energy loss in residential buildings, and building exterior wall insulation is an important way to achieve building energy conservation. Insulation and energy-saving materials are divided into three categories according to their materials: metal insulation materials, organic insulation materials, and inorganic insulation materials. Metal insulation materials are in short supply and expensive, and the cost of using them as building insulation materials is high. At present, building insulation materials, especially exterior wall insulation materials, are still mainly organic materials, of which polystyrene has a market share of about 90% and polyurethane has a market share of about 10%. However, organic insulation materials are easy to burn, high temperatures easily produce toxic gases, and have poor aging resistance and fire resistance, making them unsuitable for long-term use as building insulation materials. As a new type of inorganic insulation material, microcrystalline foamed ceramic panels have the advantages of fireproofing and insulation, low thermal conductivity, non-toxic and odorless, low water absorption, and good anti-corrosion and moisture-proof properties. With the continuous improvement of the preparation process and performance indicators of microcrystalline foamed materials, the market application prospects of microcrystalline foamed materials are good.
[0003] However, the production process of microcrystalline foam materials is relatively complicated, requiring the raw materials to be melted at high temperature, followed by calendering, crystallization, annealing and other operations before the material can be formed. Moreover, there are many factors that affect the preparation of microcrystalline foam materials, such as raw material particle size, raw material ratio, firing temperature, etc. If any of these conditions do not meet the requirements, microcrystalline foam materials cannot be prepared. The existing technology for preparing microcrystalline foam materials has relatively strict control over raw materials, processes and equipment conditions, which results in excessively high costs for preparing microcrystalline foam materials. Summary of the invention
[0004] The main purpose of the present invention is to provide a microcrystalline foam material and a preparation method thereof, so as to solve the problem of high preparation cost of microcrystalline foam material in the prior art.
[0005] In order to achieve the above-mentioned purpose, according to the first aspect of the present invention, a method for preparing a microcrystalline foam material is provided, the preparation method comprising: S1) drying and grinding the gasification slag and the filter cake respectively, and then mixing them with auxiliary materials to obtain a first mixture; S2) sintering the first mixture to obtain a microcrystalline foam material.
[0006] Furthermore, the drying comprises: drying the coal gasification slag to a water content of 1-15 wt %; and drying the filter cake to a water content of 1-20 wt %.
[0007] Furthermore, the grinding includes grinding the coal gasification coarse slag and the filter cake respectively until D90 is less than 74 μm and the maximum particle size is less than 250 μm.
[0008] Furthermore, the firing temperature is 1100° C.-1250° C. and the firing time is 1-8 hours.
[0009] Further, the filter cake is a filter cake derived from the coal gas industry for filtering synthesis gas; preferably, the composition of the coal gasification crude slag includes 50-60wt% SiO2, 15-25wt% Al2O3, 6-15wt% CaO, 6-10wt% Fe2O3, 1-3wt% K2O, 1.5-5wt% MgO, 1-2.5wt% Na2O, 0.5-2wt% TiO2 and 0.2-1wt% SO3;
[0010] Preferably, the composition of the filter cake includes 50-60wt% SiO2, 5-25wt% Al2O3, 6-15wt% CaO, 6-10wt%, 6-10wt% Fe2O3, 2-3wt% K2O, 1.5-5wt% MgO, 1-3wt% Na2O, 0.5-2wt% TiO2 and 0.2-1.5wt% SO3.
[0011] Furthermore, the auxiliary materials include silica sand, a foaming agent and a foam stabilizer.
[0012] Further, the mixing includes: mixing 5-30 parts of coal gasification crude slag, 20-65 parts of filter cake, 10-50 parts of silica sand, 0.1-2 parts of foaming agent, and 3-10 parts of foam stabilizer by mass to obtain a first mixture.
[0013] Further, the silica sand includes desert sand and / or quartz sand.
[0014] Further, the foaming agent includes limestone and / or silicon carbide; preferably, the foam stabilizing agent includes one or more of iron oxide, titanium dioxide, tripotassium phosphate, sodium phosphate or boric acid.
[0015] According to a second aspect of the present invention, a microcrystalline foam material is provided. The microcrystalline foam material is a microcrystalline foam material obtained by any of the above-mentioned methods for preparing a microcrystalline foam material.
[0016] By applying the technical solution of the present invention, the raw materials for preparing the microcrystalline foam material, the coarse coal gasification slag and the filter cake, are dried and ground in sequence, and then mixed with auxiliary materials and fired to obtain the microcrystalline foam material of the present application. The preparation method of the present application has simple steps, and the waste gasification coarse coal gasification slag and the filter cake generated in the coal mining industry are used as the raw materials of the microcrystalline foam material. The prepared microcrystalline foam material can meet the application requirements. Compared with the prior art, the preparation method of the microcrystalline foam material of the present application further reduces the cost of preparing the material, and is more suitable for promotion in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0018] Figure 1 A schematic diagram of the particle size distribution of the coal gasification coarse slag of Example 1 of the present application specification is shown.
[0019] Figure 2 A schematic diagram of the filter cake particle size distribution of Example 1 of the present application specification is shown.
[0020] Figure 3 The surface morphology of the microcrystalline foamed material of Groups 1-3 of Example 2 of the present application is shown.
[0021] Figure 4 The surface morphology of the microcrystalline foamed materials of Groups 4 to 8 of Example 3 of the present application is shown.
[0022] Figure 5 The X-ray diffraction diagram of the microcrystalline foamed material of Group 8 of Example 3 of the present application specification is shown.
[0023] Figure 6 The morphological diagrams of the microcrystalline foam material of Example 4 of the present application specification subjected to firing tests at different temperatures are shown.
[0024] Figure 7 The morphology of the microcrystalline foamed material of Groups 1-4 in Comparative Example 1 of the present application specification is shown. DETAILED DESCRIPTION
[0025] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0026] Due to the special properties of microcrystalline foam materials and the increasing requirements of industrial demand for the performance indicators of microcrystalline foam materials, the existing technology for preparing microcrystalline foam materials has relatively strict requirements on raw materials, equipment and process conditions in the preparation process, the steps are relatively complicated, and the energy consumption of the equipment is high, resulting in excessively high costs for preparing and producing microcrystalline foam materials. The technology for preparing microcrystalline foam materials in the prior art is as follows.
[0027] Patent application CN105418150A discloses a building thermal insulation material, which includes 36-45% of ordinary silicate cement, 15-25% of ceramic waste, 15-25% of fly ash, 5-10% of magnesium oxide, 5-8% of hydrogen peroxide, and 2-6% of modified additives by mass percentage. Its preparation process is as follows: the above-mentioned mixture is ball-milled in a ball mill to make the raw materials evenly mixed, water is added and stirred evenly, and then hydrogen peroxide is added and stirred quickly to obtain foamed cement slurry. The foamed cement slurry is poured into a mold, formed at room temperature, and then fired at 800°C, cooled naturally, and cut into products. The microcrystalline foam material prepared in this patent application has the disadvantages of large and uneven pores, low thermal insulation performance, poor strength, and poor stability.
[0028] Patent application CN108383496A discloses a method for producing foam ceramics using slag, iron tailings and silicon carbide foaming agent. The specific method is: weigh 6-7 parts of ironmaking slag, 2.8-3.8 parts of iron tailings and 0.15-0.25 parts of silicon carbide powder by weight respectively; add the weighed materials to a ball mill and mix and grind for 4-8 hours until all the materials pass through a 200-mesh sieve; load the prepared mixture into the kiln furniture on the kiln car of the tunnel kiln or the kiln furniture on the roller rod of the roller kiln. This method of foam ceramics uses cheap and easily available ironmaking slag to mix and grind with iron tailings and silicon carbide, and sinter at high temperature to form a lightweight microcrystalline foam ceramic blank, which is finally cut and ground into an interior partition board material for prefabricated buildings. Although this patent application uses slag and iron tailings as raw materials, the volume density of the microcrystalline foam material finally prepared is 400-600Kg / m 3 , the density is large, the grinding time is too long, and the energy consumption of the equipment is high.
[0029] Patent application CN 105565829 A discloses a method for preparing a lightweight, energy-saving, and thermal insulation ceramic material. The preparation method first mixes the raw materials, then wet-mills the mixed raw materials, sieves them through a 40-mesh sieve after drying; spray-granulates the sieved raw materials, and then sieves them through a 60-mesh sieve; finally, the sieved raw materials are placed in a refractory mold and fired to obtain a lightweight, energy-saving, and thermal insulation ceramic material. The patent application uses a complex process of wet ball milling and spray granulation, consumes a lot of water resources and natural gas, and has a high preparation cost, which is not conducive to green development.
[0030] Patent application CN 104817339 A discloses a Class A inorganic fireproof foam insulation board produced using tailings and a preparation method thereof, wherein the raw material composition is 40-60 parts by weight of copper tailings, 30-50 parts by weight of bauxite tailings, 0-15 parts by weight of silica sand, 2-10 parts by weight of industrial soda ash and 0.2-1.5 parts by weight of high-temperature foaming agent, and the preparation process uses the "wet ball milling-spray granulation-high-temperature foaming" process for production. This patent application uses copper tailings and bauxite tailings as the main raw materials, adopts the traditional wet process, and consumes a large amount of water resources.
[0031] Patent application CN 104790544 A prepares clay, graphite, red clay and limestone into tiny fine powders, mixes them evenly in proportion, and then evenly spreads the fine powder mixture in a firing mold, and a high-strength refractory steel mesh is fixed in the mold and laid in the middle of the fine powder mixture, and the mixture and the refractory steel mesh are fired and cooled in one piece in a high-temperature firing kiln. This method can enhance the overall support structure strength of the board by adjusting the strength of the steel mesh configured in the middle of the board, and enhances the safety and service life of the building board during use, but the preparation of raw materials requires the consumption of natural resources such as clay and red clay, and high-strength refractory steel mesh needs to be added to the raw materials, and the preparation cost is too high.
[0032] As mentioned in the background technology, stone powder, clay, and Guanyin soil are often used as raw materials in the preparation of microcrystalline foam materials, which consumes natural resources. Moreover, the large pieces of raw materials need to be crushed and ground for a long time, and the equipment energy consumption is high. The above-mentioned prior art also often uses wet ball milling and spray granulation methods. This wet process consumes a lot of water, which increases the cost of preparation. Therefore, the preparation method of microcrystalline foam materials in the prior art is relatively high in cost, which is easy to cause waste of resources and loss of equipment, is not conducive to green development, and is not suitable for promotion and application in industrialized amplification production. Therefore, in this application, the inventor attempts to develop a new preparation method for microcrystalline foam materials, using waste gasification slag produced in the coal gas industry as raw materials. Through the preparation method of this application, it is possible to successfully prepare microcrystalline foam materials that meet the requirements of the application. Compared with the prior art, the preparation cost is lower and more suitable for industrial production. Based on this, a series of protection schemes of this application are proposed.
[0033] In a first typical embodiment of the present application, a method for preparing a microcrystalline foam material is provided, the preparation method comprising: S1) drying and grinding the gasification slag and the filter cake respectively, and then mixing them with auxiliary materials to obtain a first mixture; S2) sintering the first mixture to obtain a microcrystalline foam material.
[0034] The raw material used in the above-mentioned preparation method is coal gasification slag, including two types: coal gasification crude slag and filter cake. It is a solid particle formed by the high-temperature physical and chemical transformation of inorganic minerals in coal after the gasification reaction of coal and oxygen at a high temperature of 1200°C-1500°C in a gasifier. Coal gasification crude slag is produced at the slag discharge port of the gasifier, and the filter cake is the waste produced by the dust removal and filtration of the synthesis gas. At present, the treatment methods of gasification ash are mainly storage and landfill, and the technology has not yet been applied on a large scale industrially. A large amount of gasification slag solid waste causes waste of land resources and affects the environment. The present application utilizes coal gasification crude slag and filter cake as raw materials for the preparation of microcrystalline foaming materials, which saves the cost of raw materials, and the prepared microcrystalline foaming materials meet the application requirements.
[0035] The initial gasification slag has a water content of usually more than 20%, and the initial filter cake has a water content of usually more than 50%. Both have high water contents and need to be dried before using them as raw materials for microcrystalline foaming materials. During the drying process, the gasification slag and the filter cake do not burn, explode, or produce toxic gases. They can be dried using any common drying equipment known to those skilled in the art. The present application preferably uses a wear-resistant steam pipe rotary dryer.
[0036] This application aims at the difference in particle size distribution and hardness of the initial gasification slag and the initial filter cake, and adopts a separate grinding method to make them meet the particle size parameter requirements of the microcrystalline foaming raw material to achieve the purpose of reducing energy consumption. Since the gasification slag and the filter cake do not have the hazards of combustion, explosion, toxicity, etc., any grinding equipment known to those skilled in the art can be used to grind the gasification slag and the filter cake, and there are no special requirements.
[0037] The present application utilizes coal gasification slag as a raw material for preparing microcrystalline foaming materials. Through the preparation method of the present application, the crude coal gasification slag and filter cake are first dried and ground before being pre-treated to make them conform to the requirements for preparing microcrystalline foaming materials for composite industrial applications. The preparation method of the present application has low raw material cost and a simple preparation process, which not only reduces the cost of preparing such microcrystalline foaming materials, but also solves the waste of land resources and the impact on the environment caused by the storage and landfilling of coal gasification slag. The concept of composite green development is more suitable for promotion to industrialized scale-up production compared with the preparation method of microcrystalline foaming materials in the prior art.
[0038] In a preferred embodiment, drying comprises: drying the coal gasification slag to a moisture content of 1-15wt%, including but not limited to 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%; drying the filter cake to a moisture content of 1-20wt%, including but not limited to 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.
[0039] The present application reduces the moisture content of the crude coal gasification slag to below 15%. The moisture content of the crude coal gasification slag is reduced to below 15% and the moisture content of the filter cake is reduced to below 20%. Controlling the moisture content within the above range is beneficial to the subsequent grinding and mixing of raw materials, and can avoid excessive drying conditions, resulting in equipment loss and energy waste.
[0040] In a preferred embodiment, the grinding includes grinding the coal gasification coarse slag and the filter cake respectively until D90 is less than 74 μm and the maximum particle size is less than 250 μm.
[0041] After the coal gasification coarse slag and filter cake are ground separately, their particle sizes are controlled within the above range, which can meet the parameter requirements of the microcrystalline foam material, and is beneficial to improving the subsequent mixing effect with auxiliary materials and the firing effect, so as to promote the overall performance of the microcrystalline foam material.
[0042] In a preferred embodiment, the firing temperature is 1100℃-1250℃, including but not limited to 1100℃, 1120℃, 1130℃, 1140℃, 1150℃, 1160℃, 1170℃, 1180℃, 1190℃, 1120℃, 1220℃, 1230℃, 1240℃ or 1250℃, preferably 1140-1250℃.
[0043] In a preferred embodiment, the firing time is 1-8 hours, including but not limited to 1, 2, 3, 4, 5, 6, 7 or 8 hours.
[0044] When preparing microcrystalline foaming materials, they usually need to be fired at high temperatures. In theory, the higher the firing temperature is set, the better the firing effect will be. However, too high a firing temperature will easily damage the firing equipment, shorten the service life of the equipment, and require frequent replacement, which indirectly leads to an increase in the preparation cost. The filter cake of the present application contains residual carbon, which usually has a residual carbon content of 20%-40% and a calorific value of 6MJ / Kg-8MJ / Kg. The filter cake is used as part of the raw material of the microcrystalline foaming material. During the firing of the microcrystalline foaming material, the residual carbon in the filter cake reacts with oxygen to produce gas, which helps the material foam. Moreover, during the firing process, only the energy for heating the tunnel kiln or the track kiln needs to be provided when the machine is started, so that the residual carbon in the filter cake burns, and the residual carbon burns to release heat. Subsequently, the microcrystalline foaming material is fired by relying on the heat source in the filter cake, thereby reducing the energy consumption of the firing equipment for firing the microcrystalline foaming material, extending the service life of the equipment, and further reducing the preparation cost.
[0045] The present application controls the firing temperature within the above-mentioned range, which can cause the residual carbon in the filter cake to burn, and the density, compressive strength and flexural strength of the prepared microcrystalline foam material can meet the requirements of industrial applications, avoiding the damage to the firing equipment caused by excessively high temperatures, extending the service life of the equipment, reducing energy loss, and reducing the cost of preparation.
[0046] The firing equipment mentioned above in the present application includes but is not limited to one or more of a tunnel kiln, a rail kiln or an electric furnace, or can be selected from any firing equipment known to those skilled in the art.
[0047] In a preferred embodiment, the filter cake is a filter cake derived from the coal gas industry for filtering synthesis gas; preferably, the coal gasification slag includes coal gasification crude slag and filter cake; preferably, the composition of the coal gasification crude slag includes 50-60wt% SiO2, 15-25wt% Al2O3, 6-15wt% CaO, 6-10wt% Fe2O3, 1-3wt% K2O, 1.5-5wt% MgO, 1-2.5wt% Na2O, 0 .5-2wt% TiO2 and 0.2-1wt% SO3; preferably, the ingredients of the filter cake include 50-60wt% SiO2, 5-25wt% Al2O3, 6-15wt% CaO, 6-10wt%, 6-10wt% Fe2O3, 2-3wt% K2O, 1.5-5wt% MgO, 1-3wt% Na2O, 0.5-2wt% TiO2 and 0.2-1.5wt% SO3.
[0048] In a preferred embodiment, the auxiliary materials include silica sand, a foaming agent and a foam stabilizer.
[0049] In a preferred embodiment, the mixing comprises: by weight, 5-30 parts of coal gasification crude slag (including but not limited to 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30 parts), 20-65 parts of filter cake (including but not limited to 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30 parts), 6, 27, 28, 29, 30, 31, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64 or 65 parts), 10-50 parts of silica sand (including but not limited to 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 or 50 parts), 0.1-2.0 parts of foaming agent (including but not limited to 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0. Preferably, the mass fraction of desert sand is 20-40 parts; preferably, the mass fraction of silicon carbide is 0.3-0.6 parts, more preferably 0.5 parts.
[0050] Silica sand is a substance with a high silicon content, and its main component is silicon dioxide. Adding silica sand during the preparation process can increase the SiO2 content in the microcrystalline foam material matrix, promote the formation of the glass phase of the microcrystalline foam material, improve the pore structure, and strengthen the network structure of the microcrystalline foam material matrix.
[0051] The role of the foaming agent is to promote the generation of gas in the first mixture during the subsequent firing process to form a bubble structure, thereby reducing the density of the microcrystalline foam material and improving its heat resistance.
[0052] The role of the foam stabilizer is to improve the stability of the bubble structure formed above and prevent the bubbles from merging, bursting and draining during the preparation process, thereby ensuring the uniformity and stability of the bubble structure.
[0053] In a preferred embodiment, the silica sand comprises desert sand and / or quartz sand, preferably desert sand.
[0054] In a preferred embodiment, the foaming agent comprises limestone and / or silicon carbide, preferably silicon carbide.
[0055] In a preferred embodiment, the foam stabilizer includes one or more of iron oxide, titanium dioxide, tripotassium phosphate, sodium phosphate or boric acid.
[0056] The present application controls the mixing ratio of raw materials and auxiliary materials in the microcrystalline foam material within the above-mentioned range, which is beneficial to improving the network structure strength, heat resistance, and uniformity and stability of the bubble structure of the finally prepared microcrystalline foam material.
[0057] The preparation method of the microcrystalline foam material of the present application uses coal-based solid waste gasification crude slag and filter cake as the main raw materials, reduces the consumption of natural resources such as stone powder, clay, Guanyin soil, and realizes the resource utilization of solid waste gasification slag; adopts the process of separate dehydration and separate grinding of gasification slag and filter cake to reduce the energy consumption of raw material crushing and grinding; uses the heat energy of residual carbon combustion in the filter cake as a heat source in the firing process, reduces the energy consumption of the firing process, saves energy, and the preparation process of the present application does not require spray granulation and has less water consumption. Compared with the preparation method of microcrystalline foam materials in the prior art, the overall energy consumption of the present application is lower, the steps are simple, and the cost is relatively low, which realizes the effective utilization of coal-based solid waste, conforms to the concept of green development, and is more suitable for promotion in the industrialization of microcrystalline foam materials.
[0058] In a second typical embodiment of the present application, a microcrystalline foam material is provided. The microcrystalline foam material is a microcrystalline foam material prepared by the above-mentioned method for preparing a microcrystalline foam material.
[0059] The beneficial effects of the present application will be further explained in detail below in conjunction with specific embodiments.
[0060] Unless otherwise specified, the reagents in the examples of this application are conventional commercially available products.
[0061] Example 1
[0062] The preparation methods of the microcrystalline foamed materials in the embodiments of the present application are as follows:
[0063] 1. Drying: Use a wear-resistant steam tube rotary dryer (model HZG) to reduce the moisture content of the coal gasification slag to below 15%.
[0064] The filter cake was shaken and heated by a JHCHJ-300 mixer to reduce the moisture content of the filter cake to about 40%, and then the filter cake was further dried by a ZSG rotary flash dryer to reduce the moisture content to below 20%.
[0065] 2. Grinding: The particle size distribution was tested using the German NIMBUS R ultrasonic attenuation particle size analyzer, and the particle size differential distribution and cumulative distribution were obtained. The particle size distributions of the gasification coarse slag (the gasification coarse slag of batch 1 in Table 1) and the filter cake (the filter cake of batch 1 in Table 1) were as follows: Figure 1 and Figure 2 shown.
[0066] Depend on Figure 1 and Figure 2 It can be seen that the particle size distribution of coal gasification coarse slag is mainly 800μm-1500μm, and the particle size distribution of filter cake is mainly 200μm-800μm. The coal gasification coarse slag and filter cake are ground separately. After grinding, the maximum particle size of coal gasification coarse slag and filter cake is less than 250μm, and the particle size less than 74μm accounts for more than 90%.
[0067] 3. Mixing: The ground coal gasification slag, filter cake and auxiliary materials are mixed evenly in a mixing device (model RB-600).
[0068] 4. Molding: Put the evenly mixed raw materials into a high temperature resistant mold to give the microcrystalline foam material a specific shape and size.
[0069] 5. Firing: The mold with the raw materials is sent to the orbital kiln (model YQ-018-1M3) for high-temperature foaming firing, and then naturally cooled to room temperature.
[0070] 6. Cutting: After the foamed material cools to room temperature, remove the mold and use a cutting machine (model HG-601500) to cut off the irregular parts of the foamed expansion.
[0071] 7. Grinding: Grind the edges, corners and surfaces of the cut foam material.
[0072] In this embodiment, components of different batches of coal gasification crude slag and filter cakes were tested, and the mass percentage results of each component are shown in Table 1 and Table 2, respectively.
[0073] Table 1
[0074]
[0075]
[0076] Table 2
[0077]
[0078] Example 2
[0079] This embodiment uses the coal gasification crude slag and filter cake of batch 1 in embodiment 1 as raw materials, the silica sand is desert sand, the foaming agent is silicon carbide, and the foam stabilizer is sodium phosphate.
[0080] The mass ratios of raw materials and auxiliary materials of different groups in this embodiment are shown in Table 3. The firing conditions are set as follows: heating rate 10°C / min, firing temperature 1200°C, and holding time 240min.
[0081] Table 3
[0082]
[0083] The surface morphology of groups 1-3 of this embodiment is shown in FIG. Figure 3 As shown. Among them, Figure 3 A is the microcrystalline foam material of group 1, Figure 3 B is the microcrystalline foam material of group 2. Figure 3 C is a microcrystalline foam material of group 3, consisting of Figure 3 It can be seen that when the foaming agent SiC is added, the microcrystalline foam material matrix foams evenly.
[0084] SiC reacts with O2 to generate a certain amount of SiO2, which forms a protective layer on the surface of SiC, making SiC relatively stable at a lower temperature; as the system temperature rises further, some low-melting materials in the raw materials begin to melt and produce a certain amount of liquid phase, which will destroy the SiO2 protective layer. When the system temperature reaches the lowest eutectic point of the gasification slag and the filter cake, the amount of liquid phase will increase further, and the SiO2 protective layer will be severely damaged, causing the diffusion rate of O2 to increase rapidly. The generated gas reaches equilibrium with the liquid phase, and closed pores are formed in the sample.
[0085] When the silicon carbide addition is 0.5% (Group 1, Figure 3 In Figure A), the pore shape of the prepared microcrystalline foam material is more regular, the pore size is smaller and the pore size consistency is high, indicating that the addition of 0.5% silicon carbide makes the foaming of the microcrystalline foam material matrix more uniform.
[0086] The microcrystalline foam material matrix prepared by the above groups 1 to 3 was subjected to performance testing (the testing method was the method described in the standard JG / T506-2016), and the results are shown in Table 4.
[0087] Table 4
[0088] Foaming agent content (%) <![CDATA[Bulk density (kg / m 3 )]]> Compressive strength(MPa) Flexural strength(MPa) 0.2 436.95 4.84 3.11 0.5 392.86 4.62 3.05 0.8 354.23 4.53 2.89
[0089] With the increase of SiC addition, under the same sintering temperature, heating rate and holding time, more gas is generated, which makes the porosity of the microcrystalline foam material matrix larger, resulting in lower compressive strength and flexural strength. Based on the above indicators, when the foaming agent addition amount is 0.5, the volume density of the microcrystalline foam material meets the requirement of ≤400kg / m 3 , and the compressive strength and flexural strength are relatively high.
[0090] Example 3
[0091] This embodiment uses the coal gasification crude slag and filter cake of batch 2 in embodiment 1 as raw materials, the silica sand is desert sand, the foaming agent is silicon carbide, and the foam stabilizer is sodium phosphate.
[0092] The weight ratios of raw materials and auxiliary materials of different groups in this embodiment are shown in Table 5.
[0093] The firing conditions were set as follows: heating rate 10°C / min, firing temperature 1200°C, and holding time 240min.
[0094] Table 5
[0095]
[0096] The pore morphology of the microcrystalline foam material matrix under different desert sand contents is shown in the figure below. Figure 4 As shown, Figure 4 AE in the figure respectively correspond to the pore appearance morphology of the microcrystalline foamed materials of groups 4 to 8 of this embodiment. Figure 4 It can be seen that with the increase of desert sand addition, the bubble size of the microcrystalline foam material matrix sample gradually decreases. This is because under the same firing system, with the decrease of coal gasification coarse slag and filter cake content and the increase of desert sand content, the SiO2 content in the batch increases, the viscosity of the system increases, the bubbles formed are not easy to grow, and the pore size formed is smaller.
[0097] When the amount of desert sand added is 15% or less, the cells of the microcrystalline foam material matrix are elliptical, and the bubble size distribution is uneven. When the amount of desert sand added increases to 20% or more, the cells of the microcrystalline foam material matrix are round, the bubble distribution is relatively uniform, and the formed pore structure is better. This is because as the SiO2 content in the microcrystalline foam material matrix increases, the network structure of the microcrystalline foam material matrix is strengthened.
[0098] The test results of the performance of the microcrystalline foam material matrix under different desert sand contents are shown in Table 7.
[0099] Table 6
[0100]
[0101]
[0102] The microcrystalline foam material sample of group 6 was ground into powder and analyzed by X-ray diffractometer to determine the phase composition of the microcrystalline foam material. The results are as follows: Figure 5 As shown by Figure 5 It can be seen that the physical phase composition of the microcrystalline foam material is mainly glass phase and crystal phase, and the main crystals are quartz (SiO2) and feldspar compounds.
[0103] Example 4
[0104] In this example, the raw materials and auxiliary materials of Group 2 of Example 2 were used for the firing test. The firing test of the material was carried out under the conditions of 1140°C, 1150°C, 1160°C, 1170°C and 1180°C respectively. The pore morphology of the microcrystalline foam material matrix sample at different firing temperatures is shown in the figure. Figure 6 The performance test results are shown in Table 7.
[0105] Table 7
[0106] Firing temperature (℃) <![CDATA[Density (kg / m 3 )]]> Compressive strength(MPa) Flexural strength(MPa) 1140 424.35 4.82 3.12 1150 395.13 4.54 3.08 1160 386.24 4.36 3.05 1170 371.16 4.11 2.95 1180 382.34 3.94 2.88
[0107] Example 5
[0108] The raw material ratio and parameters of Group 6 in Example 3 were subjected to a repetitive batch test using the examples of the present application, and the test was repeated 3 times. The microcrystalline foam material of the present example was tested (the testing method was the method described in the standards JG / T 506-2016 and GB6566-2010), and the specific results are shown in Table 8 (if there is only a single value in the table, it means that the test results of the materials in the batch are consistent). The volume density, compressive strength, flexural strength, and thermal conductivity of the three batches of microcrystalline foam material matrices of the present example all meet the technical requirements of the microcrystalline foam material with a strength level of MU4.5 in JG / T 506-2016, and the radioactivity meets the requirements of the main building materials in GB 6566-2010.
[0109] Table 8
[0110]
[0111]
[0112] Comparative Example 1
[0113] This comparative example uses the filter cake of batch 1 in Example 1 and the crude slag of coal gasification as raw materials, uses limestone as a foaming agent, sodium phosphate as a foam stabilizer, and no silica sand.
[0114] The quality ratios of raw materials and auxiliary materials in different groups of this comparative example are shown in Table 9.
[0115] Table 9
[0116] Group Filter cake (%) Coal gasification slag (%) limestone(%) Sodium phosphate (%) 1 84.00 / 8.00 8.00 2 75.00 10.00 10.00 5.00 3 70.00 15.00 10.00 5.00 4 60.00 20.00 15.00 5.00
[0117] The heating rate was set to 5℃ / min, the firing temperature was 1190℃, and the heat preservation was performed for 180min. When the firing temperature was lower than 1190℃, the mixed materials of groups 1-4 basically did not reach the molten state; and when the filter cake was used as the sole raw material to prepare the microcrystalline foam material matrix, the filter cake had a large burning loss, and the sample volume shrank too much after calcination. When the firing temperature reached 1190℃, the firing results were as follows: Figure 7 As shown, Figure 7 Among them, A is the microcrystalline foam material fired in group 1, B is the microcrystalline foam material fired in group 2, C is the microcrystalline foam material fired in group 3, and D is the microcrystalline foam material fired in group 4.
[0118] The first mixture in each group basically melts and foams, but the overall foaming rate is low, and with the increase of limestone content, the sample shows large bubbles on the surface and microbubbles at the bottom. The foaming is difficult to control and the overall foaming is uneven. This is because with the increase of limestone, the CaO content in the mixture increases. Excessive CaO content has an adverse effect on the foaming of the sample. Part of the CaO agglomerates during the mixing process of the mixture, and collapse may occur when the microcrystalline foam material matrix is fired.
[0119] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve the following technical effects: the preparation method of the microcrystalline foam material of the present application uses coal-based solid waste gasification crude slag and filter cake as the main raw materials, reduces the consumption of natural resources such as stone powder, clay, Guanyin soil, and realizes the resource utilization of solid waste gasification slag; adopts the process of separate dehydration and separate grinding of gasification slag and filter cake to reduce the energy consumption of raw material crushing and grinding; uses the heat energy of residual carbon combustion in the filter cake as a heat source in the firing process, reduces the energy consumption of the firing process, saves energy, and the preparation process of the present application does not require spray granulation and has less water consumption. Compared with the preparation method of microcrystalline foam material in the prior art, the overall energy consumption of the present application is lower, the steps are simple, and the cost is relatively low, which realizes the effective utilization of coal-based solid waste, conforms to the concept of green development, and is more suitable for promotion in the industrialization of microcrystalline foam materials.
[0120] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a microcrystalline foam material, characterized in that: The preparation method comprises: S1) drying and grinding the coal gasification coarse slag and the filter cake respectively, and then mixing them with auxiliary materials to obtain a first mixture; S2) firing the first mixture to obtain the microcrystalline foamed material.
2. The preparation method according to claim 1, characterized in that: The drying comprises: The coal gasification slag is dried to a moisture content of 1-15 wt %. The filter cake is dried to a moisture content of 1-20 wt%.
3. The preparation method according to claim 1, characterized in that: The grinding comprises: grinding the coal gasification coarse slag and the filter cake respectively until D90 is less than 74 μm and the maximum particle size is less than 250 μm.
4. The preparation method according to claim 1, characterized in that: The firing temperature is 1100°C-1250°C; The firing time is 1-8h.
5. The preparation method according to claim 1, characterized in that: The filter cake is a filter cake used for filtering synthesis gas in the coal gas industry; Preferably, the composition of the coal gasification crude slag includes 50-60wt% SiO2, 15-25wt% Al2O3, 6-15wt% CaO, 6-10wt% Fe2O3, 1-3wt% K2O, 1.5-5wt% MgO, 1-2.5wt% Na2O, 0.5-2wt% TiO2 and 0.2-1wt% SO3; Preferably, the composition of the filter cake includes 50-60wt% SiO2, 5-25wt% Al2O3, 6-15wt% CaO, 6-10wt%, 6-10wt% Fe2O3, 2-3wt% K2O, 1.5-5wt% MgO, 1-3wt% Na2O, 0.5-2wt% TiO2 and 0.2-1.5wt% SO3.
6. The preparation method according to claim 1, characterized in that: The auxiliary materials include silica sand, a foaming agent and a foam stabilizer.
7. The preparation method according to claim 6, characterized in that: The mixing includes: mixing, by mass, 5-30 parts of the coal gasification coarse slag, 20-65 parts of the filter cake, 10-50 parts of the silica sand, 0.1-2 parts of the foaming agent, and 3-10 parts of the foam stabilizer to obtain the first mixture.
8. The preparation method according to claim 6, characterized in that The silica sand includes desert sand and / or quartz sand.
9. The preparation method according to claim 6, characterized in that The foaming agent includes limestone and / or silicon carbide; Preferably, the foam stabilizer includes one or more of iron oxide, titanium dioxide, tripotassium phosphate, sodium phosphate or boric acid.
10. A microcrystalline foam material, characterized in that: The microcrystalline foamed material is a microcrystalline foamed material obtained by the preparation method of the microcrystalline foamed material according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-intensity microcrystal foaming fire prevention thermal insulation sheet material produced by using pottery clay and graphite and production technology thereof
CN104790544A
A-grade inorganic fireproof foam insulation board produced by tailings and preparation method of insulation board
CN104817339A
Building heat insulation material
CN105418150A
Preparation method of lightweight, energy-saving and heat-insulating ceramic material
CN105565829A
Method for producing foamed ceramic from granulated slag, iron tailings and silicon carbide foaming agent
CN108383496A